Plasticized environment-friendly paper biomass coating and preparation method thereof

By modifying the functional filler that synergizes with ferulic acid, combined with tung oil-based isocyanate and sodium alginate, a plasticized environmentally friendly paper biomass coating was prepared, which solved the insufficient barrier properties of traditional paper in the food packaging field and the environmental protection of coating materials, and achieved efficient hydrophobic, oil-resistant and mechanical strength improvements.

CN119686158AInactive Publication Date: 2025-03-25TAIXING PEIYUAN NEW MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411899114.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The application of traditional paper in the food packaging field is limited by its poor water, oil and gas barrier properties, and the existing paper coating materials have problems such as environmental protection, poor durability and insufficient mechanical strength.

Method used

A functional filler that synergizes with modified titanium dioxide nanoparticles and ferulic acid, combined with tung oil-based isocyanate and sodium alginate, was prepared by sonication and stirring.

Benefits of technology

The coating significantly improves the paper's hydrophobic and oil-resistant properties, and enhances its mechanical strength and durability while reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of paper coatings, and particularly discloses a plasticizing-replacing environment-friendly paper biomass coating and a preparation method thereof. The preparation method comprises the following steps: carrying out ultrasonic treatment on titanium dioxide nanoparticles in absolute ethyl alcohol, reacting with a modifier to obtain modified titanium dioxide, and reacting with ferulic acid and an auxiliary agent to prepare a functional filler; next, tung oil is subjected to an addition reaction to prepare tung oil-based isocyanate, the functional filler is dispersed in a sodium alginate aqueous solution, and the functional filler reacts with the tung oil-based isocyanate and the activating agent to obtain a composite carrier; and finally, mixing with a PDMS prepolymer, a flatting agent and a defoaming agent, and coating paper, so as to prepare the environment-friendly coating. The biomass coating of the plasticizing-replacing environment-friendly paper prepared by the preparation method has excellent hydrophobicity and oil resistance, the mechanical strength and durability of the paper are enhanced, and meanwhile, the biomass material is used to effectively replace plastics, so that the environmental pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of paper coatings, and more particularly to a plasticizing alternative and environmentally friendly paper biomass coating and a preparation method thereof. Background Art

[0002] In today's society, the concept of environmental protection is deeply rooted in people's minds, and the global demand for sustainable packaging materials is becoming increasingly urgent. Plastic packaging is gradually being restricted due to its difficulty in degrading and the potential harm to human health caused by the migration of plastic additives. In this context, the application of paper-based materials as a green and environmentally friendly alternative is becoming increasingly important. Paper raw materials are widely available, low-cost, easy to mass-produce, have good processability and printability, and can be recycled and reused after disposal without causing white pollution. In addition, paper is light in weight and has good cushioning properties, making it suitable for protecting goods under various transportation conditions. However, traditional paper is made from natural cellulose, has poor mechanical strength, and has a large number of hydrophilic hydroxyl groups and pores on its surface, which makes the paper have poor barrier properties to substances such as water, oil, and gas, greatly limiting the application of paper in the field of food packaging.

[0003] At present, in order to improve the comprehensive performance of paper-based materials, coatings are constructed on the surface of paper-based materials by dipping or spraying, which can effectively improve their surface properties. However, there are still some shortcomings in the preparation of paper coatings, which are specifically manifested in the following aspects: First, low surface energy modifiers mostly rely on fluorine-containing substances, which have adverse effects on the human body and the ecological environment, and their hydrophobic and oil-resistant properties are poor; second, non-renewable raw materials are usually used, which is not conducive to sustainable development and it is difficult to form a stable and high-strength bond with paper, which has limited improvement in the mechanical strength of paper; third, the durability is poor, and practical applications are restricted. In contrast, natural biomass such as oils and polysaccharides are renewable, biodegradable and non-toxic, and have great advantages in manufacturing green waterproof and oil-proof coatings for paper-based materials. These biomass materials can be optimized through reasonable formulation design and preparation process, so that paper can maintain good performance in humid and oily environments while resisting external impact and friction loss. Therefore, in response to the current problems with paper-based material coatings, it is of great significance to carry out research and development of biomass-based fluorine-free, green and environmentally friendly waterproof and oil-resistant coatings for waterproofing of paper-based materials. Summary of the Invention

[0004] In response to the deficiencies in the prior art, the present invention provides an environmentally friendly paper biomass coating that replaces plastics and has excellent hydrophobic and oil-resistant properties, thereby enhancing the mechanical strength and durability of paper. At the same time, the use of biomass materials effectively replaces plastics and reduces environmental pollution.

[0005] In a first aspect, the present invention provides a method for preparing a biomass coating for plasticized environmentally friendly paper, which adopts the following technical solution:

[0006] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0007] S1. Preparation of functional fillers:

[0008] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating for 40-60 minutes to obtain a suspension, adding a modifier dropwise at 40-50° C. under stirring, reacting for 2-4 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles;

[0009] S12, adding ferulic acid, acetyl chloride and pyridine to anhydrous ethanol, stirring continuously at 65-70° C. for 2-3 hours, then adding modified titanium dioxide nanoparticles, stirring at 40-50° C. for 4-6 hours, centrifuging, washing and drying to obtain a functional filler;

[0010] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0011] S21. Add tung oil and dibutyltin dilaurate to xylene, add hexamethylene diisocyanate dropwise at 50-60° C. while stirring, and then continue stirring at 70-80° C. under nitrogen protection for 3-5 hours, followed by reduced pressure distillation to obtain tung oil-based isocyanate;

[0012] S22, dispersing the functional filler in a sodium alginate aqueous solution, adding tung oil-based isocyanate, ultrasonically treating for 40-50 minutes, adding an activator, and continuously stirring at 30-35° C. for 3-5 hours to obtain a sodium alginate composite carrier;

[0013] S23. The sodium alginate composite carrier, PDMS prepolymer, leveling agent and defoaming agent are stirred at room temperature for 15-25 minutes, then coated on the paper surface and dried to obtain a plasticized environmentally friendly paper biomass coating.

[0014] Preferably, the modifier in step S11 is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 3-5:1.

[0015] Preferably, in step S11, the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol and modifier is 10-12:80-100:0.5-1.5.

[0016] Preferably, in step S12, the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine and modified titanium dioxide nanoparticles is 40-50:1-3:0.3-0.8:0.2-0.6:6-10.

[0017] Preferably, in step S21, the ingredients are 10-14 parts by weight of tung oil, 0.6-1 part by weight of dibutyltin dilaurate, 60-80 parts by weight of xylene, and 6-10 parts by weight of hexamethylene diisocyanate.

[0018] Preferably, the activator in step S22 is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1-1.5:1.

[0019] Preferably, the leveling agent in step S23 is at least one of BYK-348, BYK-346 and TEGO 410.

[0020] Preferably, the defoaming agent in step S23 is at least one of BYK-066N, BYK-1790 and TEGO Foamex 810.

[0021] Preferably, in step S23, the components comprise, by weight, 50-60 parts of a sodium alginate composite carrier, 10-15 parts of a PDMS prepolymer, 1-2 parts of a leveling agent, and 0.6-0.9 parts of a defoaming agent.

[0022] In a second aspect, the present invention further provides an alternative to plasticized environmentally friendly paper biomass coatings, which employs the following technical solutions:

[0023] A plasticizing alternative and environmentally friendly paper biomass coating is prepared by the above preparation method.

[0024] In summary, the present invention has the following beneficial effects:

[0025] 1. The present invention mixes a functional filler with a sodium alginate composite carrier made from tung oil-based isocyanate, a PDMS prepolymer, a leveling agent, and a defoaming agent, and then coats the mixture on paper to produce a plastic-replacing, environmentally friendly paper biomass coating. In the coating, after titanium dioxide nanoparticles are modified by a modifier, hydrophobic groups are enriched on the coating surface, significantly reducing the surface energy, causing water droplets to form a high contact angle on the coating surface and roll off quickly, effectively blocking moisture penetration and improving moisture resistance. At the same time, the modified titanium dioxide nanoparticles and ferulic acid work synergistically to construct a physical and chemical dual barrier to resist the invasion of oil molecules and enhance the oil resistance of the coating. The titanium dioxide nanoparticles also provide additional mechanical strength support, enhancing the overall stability of the coating. The film-forming properties of sodium alginate are further enhanced after reacting with tung oil-based isocyanate, and together with the functional filler, a continuous and compact film layer is formed. The polymer chains in the film layer are intertwined and cross-linked, effectively optimizing the overall performance of the coating. PDMS prepolymer, with its excellent flexibility and chemical stability, fills the microscopic pores within the coating, enhancing its density and maintaining structural integrity in the face of external mechanical stress and varying chemical environments, ensuring durability and stability. Furthermore, tung oil and sodium alginate are both biomass materials, effectively reducing environmental pollution and aligning with environmental protection.

[0026] 2. The functional filler of the present invention is prepared by reacting modified titanium dioxide nanoparticles with ferulic acid and an auxiliary agent. The modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane. The long-chain alkyl group imparts hydrophobicity to the titanium dioxide nanoparticles and improves their dispersibility in organic systems. The amino functional group of the γ-aminopropyltriethoxysilane not only strengthens the binding force between the modifier and the titanium dioxide nanoparticles but also creates active sites for subsequent chemical reactions, ensuring the smooth progress of the chemical reactions in the entire system. Ferulic acid reacts with other components to form chemical bonds and a stable network structure. It can, together with the hydrophobic components of the modified titanium dioxide nanoparticles, build a barrier against water and grease molecules, preventing moisture and grease contamination of paper. It also increases the crosslinking density of the coating system, effectively dispersing stress and improving overall mechanical properties. The good interfacial bonding between the functional filler and the tung oil-based isocyanate produced in subsequent steps of the coating further promotes the synergistic effect between the components, jointly optimizing the overall performance of the composite carrier, so that the coating can better maintain the stability and integrity of the paper while having excellent hydrophobic and oil-resistant properties.

[0027] 3. The present invention produces a composite carrier by reacting tung oil-based isocyanate, a functional filler, and an activator in an aqueous sodium alginate solution. The combined use of the two activators improves the efficiency and selectivity of the cross-linking reaction, providing a strong guarantee for achieving ideal coating properties. The tung oil-based isocyanate cross-links with the sodium alginate and functional filler to form a strong and elastic three-dimensional network structure, enhancing the mechanical strength of the coating and imparting excellent hydrophobicity and oil resistance. This effectively prevents moisture and grease from penetrating the interior of the paper, keeping it dry and clean and extending its service life. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0029] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used are purchased from conventional biochemical reagent stores unless otherwise specified. The quantitative experiments in the following examples were all repeated three times, and the data are the average or mean ± standard deviation of the three repeated experiments.

[0030] Titanium dioxide nanoparticles, brand Tianxing New Materials, CAS number 13463-67-7, were purchased from Jiangsu Tianxing New Materials Co., Ltd.;

[0031] Tung oil, brand Baihua Chemical, product number 206555147, purchased from Shandong Baihua Chemical Co., Ltd.

[0032] PDMS prepolymer, brand Zhedong, model sylgard184, was purchased from Anhui Zhiwei Technology Co., Ltd.;

[0033] BYK-348, brand BYK, Germany, product number BYK348, purchased from Green Union (Jining) Chemical Technology Co., Ltd.

[0034] BYK-346, brand BYK, Germany, product number BYK346, purchased from Green Union (Jining) Chemical Technology Co., Ltd.

[0035] TEGO 410, brand German Digo, item number 410, purchased from Green Union (Jining) Chemical Technology Co., Ltd.;

[0036] BYK-066N, brand UGREEN, model BYK-066N, purchased from UGREEN (Jining) Chemical Technology Co., Ltd.

[0037] BYK-1790, brand: German BYK, model 1790, purchased from Green Union (Jining) Chemical Technology Co., Ltd.

[0038] TEGO Foamex 810, brand German Tego, model 810, was purchased from Green Union (Jining) Chemical Technology Co., Ltd.

[0039] Example 1

[0040] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0041] S1. Preparation of functional fillers:

[0042] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating at 40 kHz for 60 minutes to obtain a suspension, controlling the stirring speed to 200 rpm, and adding a modifier dropwise at a rate of 1 drop / second at 40° C., reacting for 4 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier is 10:80:0.5, and the modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 3:1;

[0043] S12, adding ferulic acid, acetyl chloride, and pyridine to anhydrous ethanol, controlling the stirring speed to 300 rpm, and adding modified titanium dioxide nanoparticles after continuous stirring at 65° C. for 3 h. After stirring at 40° C. for 6 h, centrifugation, washing, and drying to obtain a functional filler, wherein the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and modified titanium dioxide nanoparticles is 40:1:0.3:0.2:6;

[0044] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0045] S21. Add 10 parts of tung oil and 0.6 parts of dibutyltin dilaurate to 60 parts of xylene in parts by weight. Under stirring at 200 rpm, add 6 parts of hexamethylene diisocyanate dropwise at a rate of 2 drops / second at 50°C. Continue stirring at 70°C under nitrogen protection for 5 hours and then perform reduced pressure distillation to obtain tung oil-based isocyanate.

[0046] S22. Dispersing 25 parts of a functional filler in 80 parts of a 5% by mass sodium alginate aqueous solution, adding 10 parts of tung oil-based isocyanate, ultrasonically treating at 40 kHz for 50 min, adding 1 part of an activator, controlling the stirring speed to 200 rpm, and continuously stirring at 30° C. for 5 h to obtain a sodium alginate composite carrier, wherein the activator consists of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1:1;

[0047] S23. According to parts by weight, 50 parts of sodium alginate composite carrier, 10 parts of PDMS prepolymer, 1 part of TEGO 410 and 0.6 parts of TEGO Foamex 810 were mixed, and the stirring speed was controlled to 100 rpm. After stirring at room temperature for 25 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0048] Example 2

[0049] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0050] S1. Preparation of functional fillers:

[0051] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating at 45 kHz for 55 minutes to obtain a suspension, controlling the stirring speed to 225 rpm, and adding a modifier dropwise at a rate of 1.2 drops / second at 48°C while stirring, reacting for 3.8 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier is 11:85:0.8, and the modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 4:1;

[0052] S12, adding ferulic acid, acetyl chloride, and pyridine to anhydrous ethanol, controlling the stirring speed to 325 rpm, and continuously stirring at 67° C. for 2.8 hours, then adding modified titanium dioxide nanoparticles, stirring at 42° C. for 5.7 hours, and then centrifuging, washing, and drying to obtain a functional filler, wherein the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and modified titanium dioxide nanoparticles is 42:2:0.5:0.3:7;

[0053] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0054] S21. Add 11 parts of tung oil and 0.7 parts of dibutyltin dilaurate to 62 parts of xylene in parts by weight. While stirring at 250 rpm, add 7 parts of hexamethylene diisocyanate dropwise at a rate of 3 drops per second at 54° C., and continue stirring at 74° C. under nitrogen protection for 4.6 hours, followed by reduced pressure distillation to obtain tung oil-based isocyanate.

[0055] S22. Dispersing 26 parts of a functional filler in 85 parts of a 4.6% sodium alginate aqueous solution by weight, adding 14 parts of tung oil-based isocyanate, and ultrasonically treating the mixture at 45 kHz for 47 minutes, adding 3 parts of an activator, controlling the stirring speed to 225 rpm, and continuously stirring at 32° C. for 4.5 hours to obtain a sodium alginate composite carrier, wherein the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1.2:1;

[0056] S23. According to weight parts, 52 parts of sodium alginate composite carrier, 11 parts of PDMS prepolymer, 1.2 parts of BYK-346 and 0.7 parts of BYK-1790 were mixed, and the stirring speed was controlled to 125 rpm. After stirring at room temperature for 23 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0057] Example 3

[0058] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0059] S1. Preparation of functional fillers:

[0060] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating at 55 kHz for 40 minutes to obtain a suspension, controlling the stirring speed to 300 rpm, and adding a modifier dropwise at a rate of 2 drops / second at 50° C., reacting for 2 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier is 12:100:1.5, and the modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 5:1;

[0061] S12, adding ferulic acid, acetyl chloride, and pyridine to anhydrous ethanol, controlling the stirring speed to 400 rpm, and adding modified titanium dioxide nanoparticles after continuous stirring at 70° C. for 2 h. After stirring at 50° C. for 4 h, centrifugation, washing, and drying are performed to obtain a functional filler, wherein the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and modified titanium dioxide nanoparticles is 50:3:0.8:0.6:10;

[0062] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0063] S21. Add 14 parts of tung oil and 1 part of dibutyltin dilaurate to 80 parts of xylene in parts by weight. Under stirring at a speed of 300 rpm, add 10 parts of hexamethylene diisocyanate dropwise at a rate of 4 drops / second at 60°C. Stirring is continued at 80°C for 3 hours under nitrogen protection, and then vacuum distillation is performed to obtain tung oil-based isocyanate.

[0064] S22. Dispersing 30 parts of a functional filler in 80 parts of a 5% by mass sodium alginate aqueous solution, adding 20 parts of tung oil-based isocyanate, and ultrasonically treating the mixture at 55 kHz for 40 min, adding 5 parts of an activator, controlling the stirring speed to 300 rpm, and continuously stirring at 35° C. for 3 h to obtain a sodium alginate composite carrier, wherein the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1.5:1;

[0065] S23. According to weight parts, 60 parts of sodium alginate composite carrier, 15 parts of PDMS prepolymer, 2 parts of BYK-348 and 0.9 parts of BYK-066N were mixed, and the stirring speed was controlled to 200 rpm. After stirring at room temperature for 15 minutes, the mixture was applied to the surface of paper and dried to obtain an alternative plasticized environmentally friendly paper biomass coating.

[0066] Example 4

[0067] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0068] S1. Preparation of functional fillers:

[0069] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating at 55 kHz for 40 minutes to obtain a suspension, controlling the stirring speed to 300 rpm, and adding a modifier dropwise at a rate of 2 drops / second at 50° C., reacting for 2 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier is 12:90:1.5, and the modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 4:1;

[0070] S12, adding ferulic acid, acetyl chloride, and pyridine to anhydrous ethanol, controlling the stirring speed to 400 rpm, and adding modified titanium dioxide nanoparticles after continuous stirring at 70° C. for 2 h. After stirring at 50° C. for 4 h, centrifugation, washing, and drying are performed to obtain a functional filler, wherein the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and modified titanium dioxide nanoparticles is 48:3:0.6:0.5:8;

[0071] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0072] S21. Add 14 parts of tung oil and 0.8 parts of dibutyltin dilaurate to 75 parts of xylene in parts by weight. Under stirring at a speed of 300 rpm, add 10 parts of hexamethylene diisocyanate dropwise at a rate of 3 drops / second at 60°C. Stirring is continued at 80°C for 3 hours under nitrogen protection, and then vacuum distillation is performed to obtain tung oil-based isocyanate.

[0073] S22. Dispersing 28 parts of a functional filler in 100 parts of a 3.5% sodium alginate aqueous solution by weight, adding 18 parts of tung oil-based isocyanate, and ultrasonically treating the mixture at 55 kHz for 40 min, then adding 4 parts of an activator, controlling the stirring speed to 300 rpm, and continuously stirring at 35° C. for 3 h to obtain a sodium alginate composite carrier, wherein the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1.5:1;

[0074] S23. According to weight parts, 60 parts of sodium alginate composite carrier, 14 parts of PDMS prepolymer, 2 parts of BYK-348 and 0.8 parts of BYK-066N were mixed, and the stirring speed was controlled to 200 rpm. After stirring at room temperature for 20 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0075] Comparative Example 1

[0076] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0077] S1. Preparation of functional fillers:

[0078] Titanium dioxide nanoparticles were added to anhydrous ethanol and ultrasonically treated at 55 kHz for 40 minutes to obtain a suspension. A modifier was added dropwise at a rate of 2 drops / second at 50° C. while stirring at a speed of 300 rpm. The suspension was reacted for 2 hours and then centrifuged, washed, and dried to obtain a functional filler, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier was 12:90:1.5, and the modifier was composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 4:1.

[0079] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0080] S21. Add 14 parts of tung oil and 0.8 parts of dibutyltin dilaurate to 75 parts of xylene in parts by weight. Under stirring at a speed of 300 rpm, add 10 parts of hexamethylene diisocyanate dropwise at a rate of 3 drops / second at 60°C. Stirring is continued at 80°C for 3 hours under nitrogen protection, and then vacuum distillation is performed to obtain tung oil-based isocyanate.

[0081] S22. Dispersing 28 parts of a functional filler in 100 parts of a 3.5% sodium alginate aqueous solution by weight, adding 18 parts of tung oil-based isocyanate, and ultrasonically treating the mixture at 55 kHz for 40 min, then adding 4 parts of an activator, controlling the stirring speed to 300 rpm, and continuously stirring at 35° C. for 3 h to obtain a sodium alginate composite carrier, wherein the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1.5:1;

[0082] S23. According to weight parts, 60 parts of sodium alginate composite carrier, 14 parts of PDMS prepolymer, 2 parts of BYK-348 and 0.8 parts of BYK-066N were mixed, and the stirring speed was controlled to 200 rpm. After stirring at room temperature for 20 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0083] Comparative Example 2

[0084] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0085] S1. Preparation of functional fillers:

[0086] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating at 55 kHz for 40 minutes to obtain a suspension, controlling the stirring speed to 300 rpm, and adding a modifier dropwise at a rate of 2 drops / second at 50° C., reacting for 2 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier is 12:90:1.5, and the modifier is composed of γ-aminopropyltriethoxysilane and octadecyltriethoxysilane in a mass ratio of 4:1;

[0087] S12, adding ferulic acid, acetyl chloride, and pyridine to anhydrous ethanol, controlling the stirring speed to 400 rpm, and adding modified titanium dioxide nanoparticles after continuous stirring at 70° C. for 2 h. After stirring at 50° C. for 4 h, centrifugation, washing, and drying are performed to obtain a functional filler, wherein the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and modified titanium dioxide nanoparticles is 48:3:0.6:0.5:8;

[0088] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0089] S21. Add 14 parts of tung oil and 0.8 parts of dibutyltin dilaurate to 75 parts of xylene in parts by weight. Under stirring at a speed of 300 rpm, add 10 parts of hexamethylene diisocyanate dropwise at a rate of 3 drops / second at 60°C. Stirring is continued at 80°C for 3 hours under nitrogen protection, and then vacuum distillation is performed to obtain tung oil-based isocyanate.

[0090] S22. Dispersing 28 parts of a functional filler in 100 parts of a 3.5% sodium alginate aqueous solution by weight, adding 18 parts of tung oil-based isocyanate, and ultrasonically treating the mixture at 55 kHz for 40 min, then adding 4 parts of an activator, controlling the stirring speed to 300 rpm, and continuously stirring at 35° C. for 3 h to obtain a sodium alginate composite carrier, wherein the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1.5:1;

[0091] S23. According to weight parts, 60 parts of sodium alginate composite carrier, 14 parts of PDMS prepolymer, 2 parts of BYK-348 and 0.8 parts of BYK-066N were mixed, and the stirring speed was controlled to 200 rpm. After stirring at room temperature for 20 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0092] Comparative Example 3

[0093] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0094] S1. Preparation of functional fillers:

[0095] Ferulic acid, acetyl chloride, and pyridine were added to anhydrous ethanol, and the stirring speed was controlled to be 400 rpm. Titanium dioxide nanoparticles were added after continuous stirring at 70°C for 2 hours. The mixture was stirred at 50°C for 4 hours, and then centrifuged, washed, and dried to obtain a functional filler. The mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and titanium dioxide nanoparticles was 48:3:0.6:0.5:8.

[0096] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0097] S21. Add 14 parts of tung oil and 0.8 parts of dibutyltin dilaurate to 75 parts of xylene in parts by weight. Under stirring at a speed of 300 rpm, add 10 parts of hexamethylene diisocyanate dropwise at a rate of 3 drops / second at 60°C. Stirring is continued at 80°C for 3 hours under nitrogen protection, and then vacuum distillation is performed to obtain tung oil-based isocyanate.

[0098] S22. Dispersing 28 parts of a functional filler in 100 parts of a 3.5% sodium alginate aqueous solution by weight, adding 18 parts of tung oil-based isocyanate, and ultrasonically treating the mixture at 55 kHz for 40 min, then adding 4 parts of an activator, controlling the stirring speed to 300 rpm, and continuously stirring at 35° C. for 3 h to obtain a sodium alginate composite carrier, wherein the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1.5:1;

[0099] S23. According to weight parts, 60 parts of sodium alginate composite carrier, 14 parts of PDMS prepolymer, 2 parts of BYK-348 and 0.8 parts of BYK-066N were mixed, and the stirring speed was controlled to 200 rpm. After stirring at room temperature for 20 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0100] Comparative Example 4

[0101] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0102] S1. Preparation of functional fillers:

[0103] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating at 55 kHz for 40 minutes to obtain a suspension, controlling the stirring speed to 300 rpm, and adding a modifier dropwise at a rate of 2 drops / second at 50° C., reacting for 2 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier is 12:90:1.5, and the modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 4:1;

[0104] S12, adding ferulic acid, acetyl chloride, and pyridine to anhydrous ethanol, controlling the stirring speed to 400 rpm, and adding modified titanium dioxide nanoparticles after continuous stirring at 70° C. for 2 h. After stirring at 50° C. for 4 h, centrifugation, washing, and drying are performed to obtain a functional filler, wherein the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and modified titanium dioxide nanoparticles is 48:3:0.6:0.5:8;

[0105] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0106] S21. Dispersing 28 parts of a functional filler in 100 parts of a 3.5% sodium alginate aqueous solution by weight, adding 18 parts of tung oil, and ultrasonically treating the mixture at 55 kHz for 40 minutes, then adding 4 parts of an activator, controlling the stirring speed to 300 rpm, and continuously stirring at 35° C. for 3 hours to obtain a sodium alginate composite carrier, wherein the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1.5:1;

[0107] S22. According to weight parts, 60 parts of sodium alginate composite carrier, 14 parts of PDMS prepolymer, 2 parts of BYK-348 and 0.8 parts of BYK-066N were mixed, and the stirring speed was controlled to 200 rpm. After stirring at room temperature for 20 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0108] Comparative Example 5

[0109] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0110] S1. Preparation of functional fillers:

[0111] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating at 55 kHz for 40 minutes to obtain a suspension, controlling the stirring speed to 300 rpm, and adding a modifier dropwise at a rate of 2 drops / second at 50° C., reacting for 2 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier is 12:90:1.5, and the modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 4:1;

[0112] S12, adding ferulic acid, acetyl chloride, and pyridine to anhydrous ethanol, controlling the stirring speed to 400 rpm, and adding modified titanium dioxide nanoparticles after continuous stirring at 70° C. for 2 h. After stirring at 50° C. for 4 h, centrifugation, washing, and drying are performed to obtain a functional filler, wherein the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and modified titanium dioxide nanoparticles is 48:3:0.6:0.5:8;

[0113] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0114] S21. Add 14 parts of tung oil and 0.8 parts of dibutyltin dilaurate to 75 parts of xylene in parts by weight. Under stirring at a speed of 300 rpm, add 10 parts of hexamethylene diisocyanate dropwise at a rate of 3 drops / second at 60°C. Stirring is continued at 80°C for 3 hours under nitrogen protection, and then vacuum distillation is performed to obtain tung oil-based isocyanate.

[0115] S22. Dispersing 28 parts of a functional filler in 100 parts of tetrahydrofuran, adding 18 parts of tung oil-based isocyanate, ultrasonically treating at 55 kHz for 40 minutes, adding 4 parts of an activator, controlling the stirring speed to 300 rpm, and continuously stirring at 35° C. for 3 hours to obtain a sodium alginate composite carrier, wherein the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1.5:1;

[0116] S23. According to weight parts, 60 parts of sodium alginate composite carrier, 14 parts of PDMS prepolymer, 2 parts of BYK-348 and 0.8 parts of BYK-066N were mixed, and the stirring speed was controlled to 200 rpm. After stirring at room temperature for 20 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0117] Comparative Example 6

[0118] A method for preparing a plasticized environmentally friendly paper biomass coating comprises the following steps:

[0119] S1. Preparation of functional fillers:

[0120] S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating at 55 kHz for 40 minutes to obtain a suspension, controlling the stirring speed to 300 rpm, and adding a modifier dropwise at a rate of 2 drops / second at 50° C., reacting for 2 hours, and then centrifuging, washing, and drying to obtain modified titanium dioxide nanoparticles, wherein the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol, and modifier is 12:90:1.5, and the modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 4:1;

[0121] S12, adding ferulic acid, acetyl chloride, and pyridine to anhydrous ethanol, controlling the stirring speed to 400 rpm, and adding modified titanium dioxide nanoparticles after continuous stirring at 70° C. for 2 h. After stirring at 50° C. for 4 h, centrifugation, washing, and drying are performed to obtain a functional filler, wherein the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine, and modified titanium dioxide nanoparticles is 48:3:0.6:0.5:8;

[0122] S2. Preparation of environmentally friendly biomass coating for plasticized paper

[0123] S21. Add 14 parts of tung oil and 0.8 parts of dibutyltin dilaurate to 75 parts of xylene in parts by weight. Under stirring at a speed of 300 rpm, add 10 parts of hexamethylene diisocyanate dropwise at a rate of 3 drops / second at 60°C. Stirring is continued at 80°C for 3 hours under nitrogen protection, and then vacuum distillation is performed to obtain tung oil-based isocyanate.

[0124] S22. Dispersing 28 parts of a functional filler in 100 parts of a 3.5% sodium alginate aqueous solution by weight, adding 18 parts of tung oil-based isocyanate, ultrasonically treating the mixture at 55 kHz for 40 min, adding 4 parts of N-hydroxysuccinimide, controlling the stirring speed to 300 rpm, and continuously stirring at 35° C. for 3 h to obtain a sodium alginate composite carrier;

[0125] S23. According to weight parts, 60 parts of sodium alginate composite carrier, 14 parts of PDMS prepolymer, 2 parts of BYK-348 and 0.8 parts of BYK-066N were mixed, and the stirring speed was controlled to 200 rpm. After stirring at room temperature for 20 minutes, the mixture was applied to the surface of paper and dried to obtain a plasticizing alternative and environmentally friendly paper biomass coating.

[0126] Performance Testing

[0127] The following performance tests were conducted on the plasticized environmentally friendly paper biomass coating prepared in Examples 1-4 and Comparative Examples 1-6:

[0128] 1. Oil resistance: The oil resistance of the biomass coating of the plasticized environmentally friendly paper was tested with reference to GB / T22805.2-208B standard. The test results are shown in Table 1.

[0129] 2. Water resistance: The water resistance of the biomass coating of the plasticized environmentally friendly paper was tested with reference to GB / T1540-2002 standard. The test results are shown in Table 1.

[0130] 3. Mechanical properties: The tensile strength of the biomass coating of the plasticized environmentally friendly paper was tested with reference to the GB / T453-2002 standard. The test results are shown in Table 1.

[0131] Table 1

[0132] Test items Kit Value <![CDATA[COBB(10min,g / m 2 )]]> Tensile strength (kN / m) Example 1 12 2.4 8.09 Example 2 12 2.3 8.11 Example 3 12 2.2 8.28 Example 4 12 1.9 8.42 Comparative Example 1 10 2.9 7.98 Comparative Example 2 10 3.5 7.91 Comparative Example 3 6 5.4 7.02 Comparative Example 4 4 6.1 6.58 Comparative Example 5 1 7.8 6.02 Comparative Example 6 7 4.2 7.63

[0133] From the results shown in Table 1 above, it can be seen that the comprehensive performance of the plasticized environmentally friendly paper biomass coatings prepared in Examples 1-4 of the present invention is far better than that of Comparative Examples 1-6.

[0134] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the described specific embodiments or replace them in similar ways. As long as they do not deviate from the invention or exceed the scope defined by the claims, they should all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a plasticized environmentally friendly paper biomass coating, characterized in that: The method comprises the following preparation steps: S1. Preparation of functional fillers: S11, adding titanium dioxide nanoparticles to anhydrous ethanol, ultrasonically treating for 40-60 minutes to obtain a suspension, adding a modifier dropwise at 40-50° C. under stirring, reacting for 2-4 hours, and then centrifugally washing and drying to obtain modified titanium dioxide nanoparticles; S12, adding ferulic acid, acetyl chloride and pyridine to anhydrous ethanol, stirring continuously at 65-70° C. for 2-3 hours, adding modified titanium dioxide nanoparticles, stirring at 40-50° C. for 4-6 hours, centrifuging, washing and drying to obtain a functional filler; S2. Preparation of environmentally friendly paper biomass coating for plasticization S21, adding tung oil and dibutyltin dilaurate to xylene, adding hexamethylene diisocyanate dropwise at 50-60° C. under stirring, and then continuously stirring at 70-80° C. for 3-5 hours under nitrogen protection, and then performing reduced pressure distillation to obtain tung oil-based isocyanate; S22, dispersing the functional filler in the sodium alginate aqueous solution, adding tung oil-based isocyanate, ultrasonically treating for 40-50 minutes, adding an activator, and continuously stirring at 30-35° C. for 3-5 hours to obtain a sodium alginate composite carrier; S23, stirring the sodium alginate composite carrier, PDMS prepolymer, leveling agent and defoaming agent at room temperature for 15-25 minutes, coating the mixture on the surface of paper, and drying the mixture to obtain a plasticized and environmentally friendly paper biomass coating.

2. The method for preparing the plasticized environmentally friendly paper biomass coating according to claim 1, characterized in that: In the step S11, the modifier is composed of octadecyltriethoxysilane and γ-aminopropyltriethoxysilane in a mass ratio of 3-5:

1.

3. The method for preparing the plasticized environmentally friendly paper biomass coating according to claim 1, characterized in that: In the step S11, the mass ratio of titanium dioxide nanoparticles, anhydrous ethanol and modifier is 10-12:80-100:0.5-1.

5.

4. The method for preparing the plasticized environmentally friendly paper biomass coating according to claim 1, characterized in that: In the step S12, the mass ratio of anhydrous ethanol, ferulic acid, acetyl chloride, pyridine and modified titanium dioxide nanoparticles is 40-50:1-3:0.3-0.8:0.2-0.6:6-10.

5. The method for preparing the plasticized environmentally friendly paper biomass coating according to claim 1, characterized in that: In step S21, the components include 10-14 parts of tung oil, 0.6-1 parts of dibutyltin dilaurate, 60-80 parts of xylene and 6-10 parts of hexamethylene diisocyanate in parts by weight.

6. The method for preparing the plasticized environmentally friendly paper biomass coating according to claim 1, characterized in that: In the step S22, the activator is composed of N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in a molar ratio of 1-1.5:

1.

7. The method for preparing the plasticized environmentally friendly paper biomass coating according to claim 1, characterized in that: In step S23, the leveling agent is at least one of BYK-348, BYK-346 and TEGO 410.

8. The method for preparing the plasticized environmentally friendly paper biomass coating according to claim 1, characterized in that: The defoaming agent in step S23 is at least one of BYK-066N, BYK-1790 and TEGO Foamex 810.

9. The method for preparing the plasticized environmentally friendly paper biomass coating according to claim 1, characterized in that: In the step S23, the components by weight include 50-60 parts of sodium alginate composite carrier, 10-15 parts of PDMS prepolymer, 1-2 parts of leveling agent and 0.6-0.9 parts of defoaming agent.

10. A biomass coating for replacing plasticized environmentally friendly paper, characterized in that: The invention is prepared by the method for preparing the plasticized environmentally friendly paper biomass coating as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-strength directly aluminizing water-based base coat and preparation method and application of high-strength directly aluminizing water-based base coat

    CN103866607A

  • Preparation method of biological nano coating based on half-bred micelles

    CN106046950A

  • In-situ regulated and controlled water-based super-amphiphobic coating layers and preparation method thereof

    CN111849329A

  • Water-based coating with water-proof and oil-proof performance as well as preparation method and application thereof

    CN114059386A

  • Preparation method and application of tung oil-based photocureable coating

    CN118344807A